Motivation to learn online during and after the COVID-19 pandemic - Zhaneta Chonteva; Tamara Jolevska Popov; Kate Trajkova (University American College Skopje, 2021)
The research aims to define the model and the role of motivation to learn in the online classrooms. As online courses become prevalent during the present pandemic caused by COVID-19, it is very important to search for the answers to the following questions: How can instructors design their online courses to optimize student motivation? And how can students identify and take advantage of motivational strengths in online courses? The modified version of the Motivation to Learn Online Questionnaire (MLOQ) was used to assess college students' motivation to learn during online classes. The MLOQ is adapted, in part, from the Motivated Strategies for Learning Questionnaire (MSLQ) and it was designed to assess the following dimensions: intrinsic and extrinsic goal orientation, self-efficacy and task value. These factors are based on a general cognitive view of motivation and are well-documented as influencing the quality of instruction in a traditional classroom, but they might function differently in online learning environments. Two other constructs: instructor support and social engagement are part of the MLOQ since they are relevant to the motivation to learn online. The sample consists of 184 university students recruited from 30 different online courses taught at two private universities in Skopje, the International Balkan University and University American College Skopje. Results from the confirmatory factor analysis show that the hypothesized 6-factor model has an acceptable fit to the data from this research and it can be considered when determining the optimal approach to online learning.
Keywords: 330; motivation to learn; online learning; autonomy; competence; relatedness; self-determination theory